Kontrowersje wokół ochrony przeciwpowodziowej Słubic = Argumentations around flood protection of Słubice city - Kołodziejczyk, Urszula; Warcholak, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Effective flood protection is one of the major problems related to Odra basin development. Nowadays, such protection is done, amongst others, by constructing of flood banks, binocles and polders. The thesis takes attempt to indicate the effective solutions in flood protection of Słubice city, for instance: additional polders creation, widening of the inter-bank area, or the most effective one - renaturalisation of the river valley.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); skuteczna ochrona przeciwpowodziowa; wały przeciwpowodziowe; polder; protection against floods; flood bank; binocle